Labour Exploitation and Work-Based Harm - Scott, Sam (Book collections on Project MUSE., 2018)
Though it barely registers in public political discussions, labour exploitation is a substantial and growing problem worldwide. This book looks at the issue through the lens of social harm, analysing the effects of labour exploitation in different contexts, critiquing existing approaches to the study of workplace exploitation, abuse, and forced labour, and showing the potential for using a social harm-focused approach to attempt to effect political and social change in this area.